2021
DOI: 10.1080/17480272.2021.1903993
|View full text |Cite
|
Sign up to set email alerts
|

Product platform alignment in industrialised house building

Abstract: Vertical integration of supply chains has enabled industrialised house-building companies to develop and use product platforms. Constant changes in the external business environment, such as customer needs, legal requirements and demand fluctuations, continually compel companies to strategically align their product platforms with market position and offering accordingly. Achieving alignment is often hindered by a lack of understanding of the interplay between the external business environment, product platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Stehn et al (2021) saw that two-dimensional structure but explained it as the build-up of corporate assets by using dynamic capabilities theorizing. Popovic et al (2021) also found that two-dimensional structure but expressed it as the alignment between using the IHB platform and developing it.…”
Section: Industrialized House Building Is About Efficiency and Effect...mentioning
confidence: 99%
“…Stehn et al (2021) saw that two-dimensional structure but explained it as the build-up of corporate assets by using dynamic capabilities theorizing. Popovic et al (2021) also found that two-dimensional structure but expressed it as the alignment between using the IHB platform and developing it.…”
Section: Industrialized House Building Is About Efficiency and Effect...mentioning
confidence: 99%